MEASURES AIMED AT RAISING THE PRESTIGE OF HIGHER TECHNICAL EDUCATION IN RUSSIA - Oleg V. Grigorash (Высшее образование в России, 2016)
The article considers the causes of decline in the prestige of higher technical professional education in Russia. Basing on their analysis the author proposes measures aimed at improving the quality ofhigher educational institution graduates and the status of technical specialists. These activities include: development of a strategic plan for the development of higher professional education, a system of vocational guidance of graduates of secondary educational institutions; improvement of quality of preparation of faculty and development of effective system of teacher training; measures for raising the quality of educational process and development of an effective system of graduate training; development of the obj ective criteria for the assessment of the effectiveness of university activities; development of a system of Patriotic education of students of secondary and higher educational institutions; increase of the salaries of specialists, influencing the country's economic development. The proposed measures are expected to improve the status and prestige of the profession ofhigher school teacher.